Analisa Self-Efficacy dan Disiplin Kerja terhadap Capaian Pendapatan Harian Porter Stasiun Kutoarjo - Rustomo, Rustomo; Ariana, Janah; Lesmana, Yanto (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
In the last two years, the surge in job seekers in Indonesia has increased, where job opportunities are difficult, so productive people choose jobs that can easily obtained, one of which is as a porter or porter. This research aims to analyze the porter workers at Kutoarjo Besar Station for their ability to manage emotions and thoughts regarding their work as porters with discipline in carrying out freelance work at the station. Using descriptive qualitative methods and snowballing sampling technique with observation and in-depth interviews with 4 source person from 26 porters who considered to represent all the porters at the station were taken by the station security coordinator, senior and junior porters. Data analysis was carried out before entering the field, while in the field and after finishing in the field. Data validity is carried out starting from reduction, data presentation to drawing conclusions. The results show that the freelance porters at the Besar Kutoarjo station are aware of the profession they are in so that their self-management skills are maintained, with work discipline they can still exist working at the station and the income they receive must be happy and sincere.